History of polio vaccination in Italy (Italian Journal of Public Health, 2010)
Polio, as a social disease, was first noted in Italy after the First World War (1915-18), with a consistent upward trend in the number of reported cases (Table 1, Figure 1). This situation has led to important research being undertaken in several National Hygiene Departments, in particular those located in Milan (Giovanardi, Monaci, Bergamini), Genoa (Petrilli, Agnese, Crovari), Palermo (D’Alessandro, Dardanoni), and Padua (Vendramini, Majori, Gasparini). Studies such as these, have examined the epidemiological and virological character of the illness in order to determine modalities for disease prevention. These studies demonstrated that all three poliovirus serotypes were circulating in Italy, with a higher prevalence (as a cause of paralytic disease) of poliovirus type 1 (about 80%), followed by type 3 (about 15%) and then type 2 (about 10 %). The presence of healthy carriers of the virus was very common in children (2-3%).The evidence of neutralizing antibodies in patients of different age groups confirmed that poliovirus infection was widespread. About 90% of the population over 14 years of age had antibodies against all three serotypes..